Achieving a Goal of Distinction in your Dress (Journal of Science and Technology, 2016)
The aim of this paper is to identify the essential and vital information about body proportions, body assets and body liabilities so as to realize the good features to emphasize and the flaws to improve through effective optical illusions in clothing. This study was based on the premise that many people disregard their proportions and figure types and just go for any style of dress that may not befit them. In order to achieve the above aim, pertinent literature was reviewed, and interviews conducted to investigate whether or not people consciously select their clothes on the basis of their body proportions.Thirty (30) ladies were interviewed and observed. The result was that the population studied was not individualistic in their dresses. The people had diverse criteria for selecting their clothes which largely excluded consideration of their body proportions. In discussing the results, personality analysis chart was designed for use of fashion conscious persons. This is in relation to the proportions of identified fashion models, average figures and some philosophy on ideal beauty. Besides, design elements which serve as effective tools for optical illusions and recommended design ideas for shaping selected figures have been provided to guide people to go for the most appropriate dress styles that are distinct and individualistic.